The Emerging Role of OTUB2 in Diseases: From Cell Signaling Pathway to Physiological Function - Li, Jun; Zhang, Na; Li, Meihua; Hong, Tao; Meng, Wei; Ouyang, Taohui (Frontiers in Cell and Developmental Biology, 2022)
Ovarian tumor (OTU) domain-containing ubiquitin aldehyde-binding protein Otubain2 (OTUB2) was a functional cysteine protease in the OTU family with deubiquitinase activity. In recent years, with the wide application of molecular biology techniques, molecular mechanism regulation at multiple levels of cell signaling pathways has been gradually known, such as ubiquitin-mediated protein degradation and phosphorylation-mediated protein activation. OTUB2 is involved in the deubiquitination of many key proteins in different cell signaling pathways, and the effect of OTUB2 on human health or disease is not clear. OTUB2 is likely to cause cancer and other malignant diseases while maintaining normal human development and function. Therefore, it is of great value to comprehensively understand the regulatory mechanism of OTUB2 and regard it as a target for the treatment of diseases. This review makes a general description and appropriate analysis of OTUB2's regulation in different cell signaling pathways, and connects OTUB2 with cancer from the research hotspot perspective of DNA damage repair and immunity, laying the theoretical foundation for future research.